Treatment outcomes of multidrug-resistant tuberculosis patients receiving ambulatory treatment in Shenzhen, China: a retrospective cohort study - Lecai, Ji; Mijiti, Peierdun; Chuangyue, Hong; Qian, Gao; Weiguo, Tan; Jihong, Chen (Frontiers in Public Health, 2023)
Background: WHO recommended multidrug-resistant tuberculosis (MDR-TB) should be treated mainly under ambulatory model, but outcome of ambulatory treatment of MDR-TB in China was little known. Methods: The clinical data of 261 MDR-TB patients treated as outpatients in Shenzhen, China during 2010-2015 were collected and analyzed retrospectively. Results: Of 261 MDR-TB patients receiving ambulatory treatment, 71.1% (186/261) achieved treatment success (cured or completed treatment), 0.4% (1/261) died during treatment, 11.5% (30/261) had treatment failure or relapse, 8.0% (21/261) were lost to follow-up, and 8.8% (23/261) were transferred out. The culture conversion rate at six months was 85.0%. Although 91.6% (239/261) of patients experienced at least one adverse event (AE), only 2% of AEs caused permanent discontinuation of one or more drugs. Multivariate analysis showed that previous TB treatment, regimens containing capreomycin and resistance to FQs were associated with poor outcomes, while experiencing three or more AEs was associated with good outcomes. Conclusions: Good treatment success rates and early culture conversions were achieved with entirely ambulatory treatment of MDR-TB patients in Shenzhen, supporting WHO recommendations. Advantageous aspects of the local TB control program, including accessible and affordable second-line drugs, patient support, active monitoring and proper management of AEs and well-implemented DOT likely contributed to treatment success rates.